2020
DOI: 10.1111/ctr.14095
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐transplant short physical performance battery: Response to pre‐habilitation and relationship to pre‐ and early post–lung‐transplant outcomes

Abstract: Alongside surgical and medical advancements in lung transplantation, the demographics of lung-transplant candidates have shifted such that older, sicker patients with an increased co-morbidity burden have experienced increased access to transplant. 1 This has led to concern around the impact of physical and medical frailty on pre-transplant outcomes (delisting, death) and post-transplant morbidity and mortality. 2 Frailty is described as a decreased physiological reserve and increased vulnerability to major st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…Functional outcomes were lower compared to recent data of our center-based program where 6MWD was preserved during short-term prehabilitation and the SPPB improved pretransplant [20,21]. Improvements in pretransplant exercise volumes were lower with telerehabilitation than what has been seen historically in our center-based rehabilitation program (ie, increased treadmill speed and quadriceps weight used for resistance training) [4,19,20].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Functional outcomes were lower compared to recent data of our center-based program where 6MWD was preserved during short-term prehabilitation and the SPPB improved pretransplant [20,21]. Improvements in pretransplant exercise volumes were lower with telerehabilitation than what has been seen historically in our center-based rehabilitation program (ie, increased treadmill speed and quadriceps weight used for resistance training) [4,19,20].…”
Section: Discussioncontrasting
confidence: 63%
“…As only a small number of LTx recipients underwent a 6MWT three months after transplant, it is not clear if LTx recipients reach the same functional benefit exercising at home versus a center-based program of supervised exercise three days per week from hospital discharge to three months posttransplant. Historically, LTx recipients achieve a 6MWD between 64%-76% predicted three months posttransplant [1,21].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of performance-based measures of exercise capacity, physical function, and frailty with healthcare utilization in lung transplant candidates was studied in 8 studies. 10 , 14 , 45 , 51 , 53 , 60 , 63 , 64 Five studies examined the relationship of the 6MWT with hospital LOS 14 , 51 , 53 , 63 , 64 and 3 studies with ICU LOS. 51 , 63 , 65 Of those, 2 studies showed a significant relationship of a higher 6MWD with hospital LOS 51 , 64 and 1 with ICU LOS, 51 using similar cutoffs of 346 51 and 350 m 64 for the 6MWD.…”
Section: Resultsmentioning
confidence: 99%
“…Frailty poses a possible three-fold increase in mortality in lung diseases [5 ▪ ,6–8]. Incident frailty is high across ILDs and influences time to mortality [5 ▪ ,9,10 ▪▪ ,11 ▪▪ ,12 ▪▪ ,13,14,15,16,17 ▪ ] and transplant success [9,10 ▪▪ ]. Overall functional status [5 ▪ ,9,10 ▪▪ ,11 ▪▪ ,12 ▪▪ ,13,14,15,16,17 ▪ ] and ILD subtype should factor into prognostication more than age [18 ▪▪ ].…”
Section: Frailty and Health Related Quality Of Lifementioning
confidence: 99%
“…Preventing deterioration toward frailty is an important goal of ILD care [10 ▪▪ –12 ▪▪ ,14–17 ▪ ]. Central to this is the recognition and management of non-ILD health events and conditions commonly occurring in the general population (Table 1).…”
Section: Processes Of Ageing and The Impact On Interstitial Lung Diseasementioning
confidence: 99%